Alleviation of Sodium Chloride Stress by Growth Regulators in Seedlings of Clusterbean (Cymopsis tetragonoloba L. Taub) - S.S. RATHORE,; N.K. PRUTHI,; G.P.S. RATHORE, (Seed Research, 2026)
Clusterbean (Cymopsis tetragonoloba L. Taub) is an important arid legume which emerged as a new industrial cash crop. Salinity is the major barrier for crop productivity in India. An experiment conducted to test the seed germination and emergence under NaCl induced salinity and effect of different levels of IAA and GA,. Different levels of IAA and GA, were taken with combinations (0.10, 0.25, 0.50 per cent) of NaCl salinity to observe their effect on different seed quality parameters. Germination percentage decreased with increasing NaCl salinity. It also delayed the germination, root length; shoot length, fresh and dry weight of seedlings decreased with increased salinity. Both IAA and GA, alleviated adverse effect of NaCl salinity on germination as well as germination period. It also mitigated the adverse effect of salinity on root length; shoot length, fresh and dry weight of seedlings. GA, show high alleviation in comparison to IAA for seedling attributes.